“It Is My Choice to Control Myself!”: Testing the Mediating Roles of Expectancy and Value in the Association Between Perceived Choice and Self-Control Success - Chow, Tak Sang; Hui, Chin Ming; Siu, Tiffany Sok U. (Frontiers in Psychology, 2022)
Past research suggested that when individuals feel that it is their free choice to perform a task, they are more likely to succeed. However, little has been known about the effect of perceived choice of self-control and the psychological processes underlying the benefits of this perception in everyday contexts. To fill this gap, a seven-day experience sampling study (115 college students and 1,725 reported episodes of self-control) was conducted to test whether confidence in sustaining the current self-control activity (expectancy) and perceived value of current self-control (value) could mediate the link between perceived choice and success in the current self-control activity. The results of multilevel analysis suggested that the perceived choice can boost self-control success by increasing expectancy and value of self-control. These findings add mechanistic understanding of the effect of perceived choice on self-control success.